A gold-catalyzed 1, 2-acyloxy migration/intramolecular cyclopropanation/ring enlargement cascade: syntheses of medium-sized heterocycles1. Issue 73 (21st September 2015) - Sun, Yin-Wei; Tang, Xiang-Ying; Shi, Min
<x xml:space="preserve">Abstract</x> A gold catalyzed 1, 2-acyloxy migration/intramolecular cyclopropanation/ring enlargement cascade of furan substrates provides a new highly efficient procedure for the formation of ten and eleven-membered ring compounds. A new transformation type of intermolecular furan compound catalyzed by a gold catalyst was reported.